2016
DOI: 10.1155/2016/5678946
|View full text |Cite
|
Sign up to set email alerts
|

Low CD36 and LOX-1 Levels andCD36Gene Subexpression Are Associated with Metabolic Dysregulation in Older Individuals with Abdominal Obesity

Abstract: Background. Obesity study in the context of scavenger receptors has been linked to atherosclerosis. CD36 and LOX-1 are important, since they have been associated with atherogenic and metabolic disease but not fat redistribution. The aim of our study was to determinate the association between CD36 and LOX-1 in presence of age and abdominal obesity. Methods. This is a cross-sectional study that included 151 healthy individuals, clinically and anthropometrically classified into two groups by age (<30 and ≥30 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…When performing a patient classification in NW and OW, we noticed that the NT2D and patients with T2D with OW showed the lower CD36 expression levels compared to NW. These observations are in concordance with the results obtained in a study performed by Madrigal-Ruiz et al in Mexican mestizo individuals ≥ 30 years old with abdominal obesity, where they observed a CD36 mRNA subexpression (54% less) and decreased levels of soluble CD36 (sCD36) in a condition of abdominal fat and higher fasting glucose, compared with individuals with abdominal obesity < 30 years 9 . However, although sCD36 levels reflect the monocytes and macrophages CD36 expression in adipose tissue, arteries, and liver, it is possible that specific population factors such as size population, age, T2D time duration, and CD36 genetic variations may affect sCD36 concentrations 10 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When performing a patient classification in NW and OW, we noticed that the NT2D and patients with T2D with OW showed the lower CD36 expression levels compared to NW. These observations are in concordance with the results obtained in a study performed by Madrigal-Ruiz et al in Mexican mestizo individuals ≥ 30 years old with abdominal obesity, where they observed a CD36 mRNA subexpression (54% less) and decreased levels of soluble CD36 (sCD36) in a condition of abdominal fat and higher fasting glucose, compared with individuals with abdominal obesity < 30 years 9 . However, although sCD36 levels reflect the monocytes and macrophages CD36 expression in adipose tissue, arteries, and liver, it is possible that specific population factors such as size population, age, T2D time duration, and CD36 genetic variations may affect sCD36 concentrations 10 .…”
Section: Discussionsupporting
confidence: 92%
“…We also noticed that CD36 PBMC expression conversely associate with BMI, WHR, glucose, and ox-LDL. These results reinforce the findings of Madrigal and colleagues where sCD36 conversely associates with WC, total body fat mass, body fat index, and LDL-c, among other metabolic parameters in Mexican populations 9 . Some studies suggested that CD36 deficiency could be detrimental on human health, indeed, it was observed that CD36 deficient individuals present higher HbA1c plasma levels, IR, and significantly increased rate of morbidity by cardiovascular complications 12 .…”
Section: Discussionsupporting
confidence: 91%
“…Out of the 47 common genes to male and female specific to the weight gain groups, 11 relate to obesity traits and metabolic syndrome according to previous studies: LTF [49], OLFM4 [50], LCN2 [51], OLR1 [52], MMP8 [53], PDK4 [54], RNASE3 [55], APOA4 [56], CHIT1 [57], GPER1 [58] and CPT1A [59]. The gene OLAH , oleoyl-ACP hydrolase, has not been reported as obesity-trait related in GeneRif but is included in several Reactome lipid-related pathways: Metabolism of lipids and lipoproteins, Fatty acid, triacylglycerol, and ketone body metabolism, Triglyceride Biosynthesis and Fatty Acyl-CoA Biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, oxLDL/LOX-1 and other scavenger receptors participate in the generation of complicated atherosclerotic plaque through matrix metalloproteinases secretion (MMP2 and MMP9) mediated by activated macrophages present in atherosclerotic plaque [ 14 , 15 , 16 , 17 ]. However, the role of LOX-1 and oxLDLs is not only restricted to pathologies, such as atherosclerosis or endothelial dysfunction, but has also been associated with the progression of chronic pathologies, such as obesity [ 18 , 19 ], type II diabetes mellitus [ 20 , 21 ], and various types of cancer. The role of LOX-1 in cancer is related to the hallmarks of cancer, such as angiogenesis, invasion, metastasis, resisting cell death, and sustained proliferative signaling between others [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and has been addressed in depth in several reviews [ 20 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%